Optimalisasi Pertumbuhan Vegetatif dan Hasil Kedelai dengan Kombinasi Pupuk Kandang Kambing dan POC Urine Kelinci - Hilmi Aini Nurthoyibah; Aisyah; Paranita Asnur (Universitas Medan Area, 2026)
Soybean (Glycine max L.) is one of the most strategic food commodities with high economic value. However, its productivity in Indonesia remains low due to limited soil nutrient availability. Therefore, this study aimed to analyze the effects of goat manure and liquid organic fertilizer (LOF) derived from rabbit urine enriched with Microbacter alfaafa-11 (MA-11) on the growth and yield of soybean plants. The research was conducted over four months, from February to June 2024, at the Nursery of the Center for Seed Development and Plant Protection, Cibubur, East Jakarta. A randomized block design (RBD) was used with three replications and two treatment factors. The first factor was rabbit urine LOF with four levels: control (without MA-11), 40 ml/L LOF + 50 ml/L MA-11, 40 ml/L LOF + 75 ml/L MA-11, and 40 ml/L LOF + 100 ml/L MA-11. The second factor was goat manure with three levels: 126 g/polybag, 251 g/polybag, and 377 g/polybag. Observed parameters included plant height, flowering time, pod formation time, and yield-related traits such as fresh pod weight, number of root nodules, dry pod weight, weight of 100 dry seeds, number of pods, and seed diameter. The results showed that the application of rabbit urine LOF had no significant effect on all observed parameters. In contrast, goat manure application significantly affected plant height, pod weight, number of pods, dry weight, and root nodule number. The highest goat manure dose (377 g/polybag) produced the best results. This study indicates that goat manure is an effective organic fertilization alternative to improve soybean productivity.